HUBUNGAN ANTARA DERAJAT KEBUGARAN JASMANI DENGAN POLA HIDUP SEHAT PADA SISWA KELAS XI SMK PAMOR CIKAMPEK - Yuliyanika, Hidayah; Nugroho, Setio; Kusuma Yuda, Aria (Universitas Hamzanwadi, 2024)
Along with the development of science and technology (IPTEK) which makes all activities more practical, many habits in one's life ignore physical activity and a healthy lifestyle. This study aims to examine the relationship between the degree of physical fitness and students' healthy lifestyle. To answer the formulated research problems, this study used a quantitative approach with a survey method with an instrument in the form of a measurement test, a healthy lifestyle instrument using a questionnaire, while the degree of physical fitness using the Indonesian physical fitness test aged 16-19 years. The research subjects used were class XI students of SMK Pamor Cikampek totaling 30 students. Data analysis techniques using product moment correlation techniques. The results obtained showed r count 0.512 ≥ r table 0.361, at the level of significance 0.05. So it can be concluded that there is a relationship or correlation between the physical fitness variable and a healthy lifestyle. As well as in the results of the coefficient of determination (Rsquare) of 0.262 which means that the influence of the second variable is 26.2%. This means that there is a significant relationship between the degree of physical fitness and a healthy lifestyle in class XI students of SMK Pamor Cikampek.